Transport pricing to promote E-biking and reduce externalities: Insights from a GPS-tracked experiment - Jakob Roth; Laura Schwab; Beat Hintermann; Thomas Götschi; Adrian Meister; Lucas Meyer de Freitas; Kay W. Axhausen (University of Basel, Center of Business and Economics (WWZ), 2025)
This study presents results from a randomized controlled trial involving 1,085 participants in Switzerland that have access to an E-bike, a car, and public transport. The participants' transport choices are monitored by means of a GPS-based tracking app. The treatment consists in a monetary incentive that approximates the main external costs and benefits associated with transport in the spirit of a Pigovian tax. This tax reduces transport-related external costs by 6.9 %, which corresponds to 78 Swiss francs per person and year (currently equivalent to 94 US dollars). The main underlying mechanism is a mode shift away from driving towards E-biking, public transport and walking. The results are primarily driven by individuals who own an S-pedelec with support up to 45 km/h, rather than users of the more common E-bikes that provide support up to 25 km/h. The pricing also induces a travel shift towards less congested time windows
Keywords: H23; H31; I18; Q54; Q58; R41; R48; 330; Transport; Field experiment; GPS tracking; bicycle; E-bike; external costs; Pigovian taxation; transport pricing